Draft Annual Plan 1976-77 Andhra Pradesh - Planning Commission (Planning Commission, 1976)
The outlay approved by the Planning Commission for the State's Fifth Five-Year Plan was Rs 1078.51 crores. The State Government tentatively finalised the plan for Rs 1105-96 crores. In the first year 1974-75, the State Government implemented a plan of Rs 148.72 crores. According to departmental figures, the expenditure incurred was Rs 147.10 crores
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh
Finance and Planning (Planning Wing) Department Government of Andhra Pradesh